2018
DOI: 10.17547/kjsr.2018.26.4.319
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Life Changes on Post-Traumatic Stress Disorder after Disasters

Abstract: Background: This study investigated whether pre-and peri-disaster experiences influence on Post-Traumatic Stress Disorder (PTSD) and whether post-disaster stress by life changes have impact on PTSD after controlling pre-and peri-disaster factors. Methods: Data came from a sample of 1,182 respondents who experienced natural disasters (flood and typhoon) in South Korea from 2012 to 2015. The SPSS Win 22.0 program was used for descriptive analysis, t-test, Chi-square test, Pearson's correlation and logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(10 reference statements)
0
4
0
1
Order By: Relevance
“…Our findings revealed that individuals who reported higher disaster distress scores were more likely to have higher levels of depression and anxiety. Similarly, a previous study found that flood victims with greater post-traumatic stress had significantly higher levels of depression and anxiety than victims experiencing lesser posttraumatic stress (Lim & Sim, 2018). However, while the average anxiety level among young adults exposed to an earthquake was significantly higher than that of those who were not exposed, there was no significant difference in depression level between young adults exposed to the earthquake and those not exposed to it (Pistoia et al, 2018).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Our findings revealed that individuals who reported higher disaster distress scores were more likely to have higher levels of depression and anxiety. Similarly, a previous study found that flood victims with greater post-traumatic stress had significantly higher levels of depression and anxiety than victims experiencing lesser posttraumatic stress (Lim & Sim, 2018). However, while the average anxiety level among young adults exposed to an earthquake was significantly higher than that of those who were not exposed, there was no significant difference in depression level between young adults exposed to the earthquake and those not exposed to it (Pistoia et al, 2018).…”
Section: Discussionmentioning
confidence: 73%
“…In addition, indirect exposure to disasters, including the disaster experiences of family and friends, and exposure to disaster as a rescue personnel or community volunteer, is also associated with psychological symptoms (Shultz et al, 2012; Thormar et al, 2010). Prior studies have targeted individuals who directly experienced specific disasters, such as earthquakes (Kwon & Park, 2019; Thapa et al, 2018), fires (S. Y. Jeon et al, 2019), floods (Bei et al, 2013; Lim & Sim, 2018), and storms (Sirey et al, 2017). However, the present study included people who were exposed, directly or indirectly, to one or more types of disasters, by recruiting a large community sample.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study support those of previous studies that economic loss negatively affects PTSD. 7,22,23 Disaster conflict refers to a clash between an area's various members and organizations, where the regional system collapses and changes dynamically subsequent to a disaster. 18 It causes the weakening and isolation of community solidarity that leads to greater harm by reducing access to significant disasterrelated information and increasing psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…22 A meta-analysis showed that physical property loss caused by a catastrophe was a risk factor for PTSD, 7 and total asset reduction after a disaster increased its risk by 1.59 times, and by 1.71 times when experiencing economic grievances. 23 In summary, trauma, disaster conflict, and economic loss can be the main risk factors for PTSD experienced by disaster victims. Furthermore, efforts to minimize their negative influence are needed to help rapid recovery after a calamity.…”
mentioning
confidence: 99%
“…한국의 조사 결과도 이와 유사한 비율을 보고하였다. 국립재난안전연구원의 2012년부터 2015년 재난피해자들을 PTSD 증상을 살펴본 결과, 재난피해자 중 과거 정신병리 이 력이 없는 사람들 중 약 24%가 재난 후 PTSD의 임상적 증 상을 보이는 위험군으로 분류되었다 (Lim HS et al, 2018).…”
unclassified